EXPLORING THE EFFECTS OF TEACHER MOBILITY ON LEARNERS’ RIGHTS TO BASIC EDUCATION. - Rapeta, Seshoka Joseph (International Online Journal of Education and Teaching, 2025)
The purpose of this study is to explore the effects of teacher mobility on learners’ rights to basic education of learners during the redeployment of teachers. The qualitative research design of this study offers a comprehensive framework for the examination of the academic, social, and affective consequences that learners experience when teachers transition between institutions. This study employs qualitative methodologies, such as document analysis and interviews, to elucidate the intricate relationship between teacher mobility and the preservation or potential infringement of learners’ rights within the educational landscape. The results suggested that teachers who have been declared additional are no longer prioritising their teaching responsibilities and are missing classes. The most effective teachers are frequently lost as a consequence of rationalisation and redeployment. The governing body of a public school is required to ensure the development of the school and to advance its best interests by providing a quality education to all learners.